Study, Design and Manufacture Microstrip Antenna For Advance Mobile Handsets - Tuan, Tran Minh (VNU Journal of Science: Natural Sciences and Technology, 2011)
Abstract . This paper concentrates on studying, designing and manufacturing a dual – band and high – bandwidth antenna applied for advance mobile handsets. This antenna can work in GSM/UMTS bands by generating two resonant modes of 900 MHz and 1900 MHz frequencies. Antenna is printed on FR4 substrate with size of 58 mm x 80 mm, thickness of 1.6 mm and relative permittivity of 4.4. The propose antenna is experimentally studied. Keywords:  Antenna, dual-band, monopole, microstrip antenna.